Corpus Linguistic Research: Analyze The Use of Possessive Pronoun in P.S I Still Love You Novel By Jenny Han - Eksita Duta Nalindra (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
In this article, the researchers talk about the possessive pronoun found in a novel by Jenny Han entitled "P.S I Still Love You". The possessive pronoun is a type of pronoun that shows something that belongs to someone. There are 2 types of a possessive pronoun, which are possessive pronoun (absolute possessive pronoun) and possessive adjective (weak possessive pronoun). The possessive pronoun includes my, mine, your, yours, our, ours, his, her, hers, its, their, and theirs. This research using the descriptive qualitative method to help this analyses. In this research, the researcher showed the possessive pronoun that appeared in the P.S I Still Love You, a novel by Jenny Han. The researcher also divided it into its type.